SUPERVISION OF ISLAMIC EDUCATION IN IMPROVING THE QUALITY OF ISLAMIC EDUCATION - Nurlia, Tri Wahyu; Sari, Sukeng Tiyas; Supriyanto, Eko Budi; Churrohman, Taufik (PT. Antis International Publisher, 2025)
Objective: This study aims to analyze the role of Islamic education supervision in enhancing the quality of education in Islamic institutions. It explores how supervision serves as a systematic effort to assist teachers and education staff in managing learning more effectively and efficiently while also fostering Islamic character development. Methods: The research adopts a qualitative approach, emphasizing the importance of supervision grounded in Islamic values. Data collection involves literature analysis and case studies of Islamic educational institutions, focusing on the implementation and impact of supervision practices. Results: The findings indicate that well-planned, continuous, and spirituality-based supervision significantly improves the quality of education. It not only enhances academic performance but also supports the holistic development of students by integrating Islamic values into the learning process. Novelty: This study highlights the unique aspect of Islamic education supervision, which goes beyond conventional academic supervision by incorporating Islamic spiritual principles. The research underscores the significance of a values-based approach in shaping both the educational experience and the moral development of students.